2022
DOI: 10.3390/electronics11162556
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Solder Joint Reliability in 3D Packaging Memory Devices under Thermal Shock

Abstract: In 3D packaging memory devices, solder joints are critical links between the chip and the printed circuit board (PCB). Under severe working conditions, cracks inevitably occur due to thermal shock. If cracks grow in the solder joint, the chip will be disconnected with the PCB, causing its function failure. In this paper, the reliability of solder joints under thermal shock are evaluated for 3D packaging memory devices by means of the SEM and finite element analysis. As microscopically studied by the SEM, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Shuai et al [143] employed a finite element simulation and thermal shock test to evaluate the reliability of solder joints of 3D PiP memory. The results show that the main failure mechanism of solder joints was thermal fatigue failure, and cracks were caused by the accumulation of plastic and creep strain.…”
Section: The Reliability Of Coc Package Memory Under Hygrothermal Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Shuai et al [143] employed a finite element simulation and thermal shock test to evaluate the reliability of solder joints of 3D PiP memory. The results show that the main failure mechanism of solder joints was thermal fatigue failure, and cracks were caused by the accumulation of plastic and creep strain.…”
Section: The Reliability Of Coc Package Memory Under Hygrothermal Stressmentioning
confidence: 99%
“…In [53,[141][142][143][144], the reliability research of PiP packaging is mainly carried out via a combination of finite element simulation and test verification, but the number of research topics classified as thermal stress and hygrothermal stress is relatively lower than those classified as PoP and CoC packaging. In addition, due to the internal encapsulation structure of PiP packaging devices and the absence of movable components, reliability research on mechanical stress is only carried out after assembly at board level.…”
Section: The Reliability Of Coc Package Memory Under Hygrothermal Stressmentioning
confidence: 99%
“…The resistance of a metal sample with known length and area could be measured using appropriate techniques. A basic ohmmeter utilizes two contacts, one at each end of the sample, to determine resistance; however, more precise measurements can be obtained by employing a four-contact device [ 20 , 21 ].…”
Section: Electrical Characteristicsmentioning
confidence: 99%
“…The main reason of failure in solder joints comes from the thermomechanical cyclic stresses caused by a variety of components with distinct coefficients of thermal expansion (CTE) [8,9]. Many investigations have been carried out to address the damage evolution of solder joints and understand the failure mechanism, which defines the operational performance of electronics systems [10][11][12]. To provide some instances, Samavatian et al [13] found that the extra effects of creep on the fatigue mechanism led to the accelerated damage of solder joints in power semiconductors.…”
Section: Introductionmentioning
confidence: 99%